La problemática de lo ético-político en Mille plateaux - Díaz, Luis Omar (Pontificia Universidad Católica del Perú. Instituto Riva-Agüero, 2015)
The present contribution aims to clarify the ethics involved in the notionof territory, coined by Deleuze and Guattari in Mille plateaux, whose philosophical notes are taken from Spinoza’s and Nietzsche’s works. We will see that this project is sufficiently consistent and united, according to its immanent and materialistic lines. However, this ethics finds its limits, not in its internal constitution but in its tacit iden- tification with politics. Our authors conceive the existential field as crossed by political effects, therefore, all ethical acts would be, by their accounts, a political act too. And these acts will be the more perfect –more ethical and more political– the less they deal with traditional state policy. This involves reducing policy to the political, which we believe is a mistake; because, what applies to the singular-collective existence cannotcount nor compete as a substitute of the collective institutional policy.

El presente artículo da cuenta de la ética asociada a la noción de territorioelaborada por Deleuze y Guattari en Mille plateaux, cuyas notas filosóficas son spino- zistas y nietzscheanas. Veremos que este proyecto es suficientemente consistente y cohesionado, de acuerdo a sus lineamientos inmanentes y materialistas. Sin embargo, esta ética encuentra su límite, no tanto en su constitución interna como en su iden- tificación tácita con la política. Nuestros autores entienden que lo existencial está traspasado por efectos políticos, luego, todo acto ético sería de suyo político, y será tanto más pleno –más ético y más político– cuanto menos tenga que ver con la política estatal tradicional. Esto implica reducir la política a lo político, lo cual creemos que es un error, pues lo que vale muy bien para la existencia singular-colectiva, no puede valer ni competir en sí mismo como substituto de la política institucional colectiva.
Keywords: Deleuze; Ética; Guattari; Micro-Política; Política; https://purl.org/pe-repo/ocde/ford#6.03.01